The Role of Education and Mentoring In Building Leadership for Women In Uzbekistan - Fayzullaeva, Aziza (Indonesian Journal Publisher, 2025)
This article explores the impact of education on fostering women's leadership in Uzbekistan. The study findings indicate that educational programs play a crucial role in enhancing women's leadership competencies. Women pursuing higher education demonstrate a strong aspiration for leadership roles, and those who have participated in educational initiatives experience notable professional growth. Additionally, the article highlights gender as a key barrier preventing women from attaining leadership positions. Global research and best practices from developed countries suggest that the implementation of specialized leadership programs for women, along with government-led initiatives promoting gender equality, serve as effective strategies for cultivating women's leadership.